The Effect of Activators on the Mechanical Properties and Microstructure of Alkali-Activated Nickel Slag. (29th June 2020) - Xu, Liwei; Wang, Xuefang; Guan, Can; Wu, Wenda; Zhang, Lingling
Abstract : In order to mitigate problems associated with environmental pollution, alkali-activated nickel slags (AANSs) may be used as an alternative to cementitious material. However, the understanding of their mechanical properties and microstructure is currently very limited. This paper therefore explores the influence of different types and contents of three solid alkali activators, Na2 SiO3, NaOH, and Na2 SiO3 /Na2 CO3, on the compressive strength of one-part AANS. Their microstructure, hydration components, and pore structure are analyzed by means of a scanning electron microscope, an energy-dispersive spectrometer, an X-ray diffractometer, an infrared spectrometer, and a mercury analyzer. The results show that the AANS with an Na2 SiO3 /Na2 CO3 activator has a denser microstructure, lower porosity, and a smaller pore size when compared with the AANS with the Na2 SiO3 or NaOH activators. Consequently, the compressive strength of the Na2 SiO3 /Na2 CO3 sample reached a higher compressive strength (96 MPa) than that activated by Na2 SiO3 or NaOH. This strength is optimal as well as more economical as Na2 O, which increased from 0.107 mol to 0.123 mol, contributes little to compressive strength. The final part of the article discusses an optimal design for the engineering application of one-part AANS.